Thetacrypt: A Distributed Service for Threshold Cryptography - Barbaraci, Mariarosaria; Senn, Michael; Schmid, Noah; Alpos, Orestis; Cachin, Christian (Anais do Latin-American Symposium on Dependable Computing (LADC), 2025)
Threshold cryptography is a powerful and well-known technique with applications to systems relying on distributed trust. It has recently also emerged as a solution to challenges in blockchains: frontrunning prevention, managing wallet keys, and generating randomness. This work presents Thetacrypt, a middleware component that enables distributed applications to access a variety of threshold schemes via a unified, implementation-agnostic interface. The architecture of Thetacrypt natively supports non-interactive as well as interactive protocols, currently including six cryptographic schemes that span ciphers, signatures, and randomness generation. Additionally, it contains flexible adapters to an underlying networking layer compatible with peer-to-peer communication and a total-order broadcast channel. Thetacrypt serves as a controlled testbed for evaluating the performance of multiple threshold-cryptographic schemes under consistent conditions, showing how the traditional microbenchmarking approach neglects the distributed nature of the protocols and their relevance when considering the performance of real deployed systems.